Organ-specific immune-mediated reactions to polyethylene glycol and polysorbate excipients: three case reports - Rogozina, Olga; Ruiz-Fernández, Carmen; Martín-López, Susana; Akatbach-Bousaid, Ibtissam; González-Muñoz, Miguel; Ramírez, Elena (Frontiers in Pharmacology, 2024)
Drug-related acute pancreatitis (AP), acute interstitial nephritis (AIN) and drug-induced liver injury (DILI) are rare but serious adverse drug reactions (ADRs) that can have lifethreatening consequences. Although the diagnosis of these ADRs can be challenging, causality algorithms and the lymphocyte transformation test (LTT) can be employed to help with the diagnosis. In this report, we present 3 cases of drug-related AP, AIN and DILI. The first case involved a patient with AP to lacosamide and to the excipient polysorbate 80 in pantoprazole. The second case involved a patient with DILI secondary to polyethylene glycol (PEG) excipients and amoxicillin-clavulanate. In case 3, AIN was considered to be the result of sensitization to excipients. Diagnoses were made using causality algorithms and the LTT. The LTT is a useful tool for helping diagnose drugrelated AP and DILI, and it can be used to identify the specific drug or excipient causing the ADR. These cases highlight the importance of considering PEG and polysorbate excipients in the causality diagnosis of ADRs.